PEMIKIRAN PEMBAHARUAN PENDIDIKAN ISLAM KH. AHMAD DAHLAN PERSPEKTIF INTELEKTUAL MUSLIM DI INDONESIA - Husin Husin (LPPM Institut Pendidikan Nusantara Global, 2023)
This study is through a historical discretive qualitative approach to the thinking and renewal of education. KH Ahmad Dahlan is a phenomenal study of various Muslim intellectuals with various scientific approaches. The purpose of this study is to redefine the fighting spirit of the figure responsible for reforms in the world of education, and the hope is that the younger generation will not be dim in making innovations, should make the spirit of KH. Ahmad Dahlan as a torch who always blames the spirits of all the nation's children. In terminology, many education experts define the purpose of Education according to KH. H. Ahmad Dahlan argues that the purpose of Islamic education is the establishment of akhlaqul qarimah is the main goal of Islamic education. A goal is something that is expected to be achieved after an effort or activity is completed. This sentence delegates that the primacy of education lies in akhalak, and value above all, the concept of Islamic Education which is considered final (comprehensive) success if it has achieved its goal which is measurable in the form of human behavior both individually and socially. As the embodiment of Muhammad's apostolic duty, he was sent to the earth, nothing but